Shoot Growth, Gamma-Terpinene and Essential Oil Content of Satureja hortensis L. in Response to Foliar Application of FeSO4 and Citric Acid - E Radmanesh; H Naghdi Badi; E Hadavi; A Mehrafarin (Institue of Medicinal Plants, ACECR, 2015)
Background: Summer savory (Satureja hortensis L.) is one of the most important medicinal and spice plants cultivated in many parts of the world. Objective: A greenhouse experiment was conducted to study the effects of FeSO4 and citric acid application on the morphological traits and essential oil content and its component, gamma-terpinene in S. hortensis. Methods: FeSO4 in four levels (0, 3, 4 and 5 g L-1) and citric acid in four levels (0, 4, 6 and 8 mM) through foliar application were considered as two studied factors in this factorial experiment. Results: The results showed that the treatments of FeSO4, and interaction of FeSO4 and citric acid had a significant effect (p<0.01) on the all studied traits, whereas citric acid treatments only had significant effect on the essential oil content (p<0.01) and plant height (p<0.05). FeSO4 and its interaction with citric acid significantly increased these traits. The optimum level of FeSO4 fertilizer on this plant was 3 and 4 g L-1 and for citric acid was 6 and 8 mM which increased the essential oil content and its component, gamma-terpinene compared to control plants. Conclusion: Foliar application of citric acid plus FeSO4 had the capability to alter the relative percentages of the essential oil content. In general, foliar application of FeSO4 with citric acid had synergistic effect on essential oil content, its component gamma-terpinene and agro-morphological traits of S. hortensis.